Gerenciamento de resíduos sólidos como instrumento de gestão ambiental na Universidade Federal do Pará – UFPA - SANTOS, Jaqueline Sarmento dos (Universidade Federal do Pará, 2018)
Concern about the environmental performance is increasingly demanding a different approach by organizations. Pressure from governments, regulatory agencies and the general population are more pronounced. The Higher Education Institutions (HEIs) and their faculties; Institutes, departments and laboratories until sometime ago had no major concerns with the proper management of the impacts caused by its activities. The environmental management with the management of waste and other environmental aspects are basic tools for a positive environmental performance is achieved. The objective of this research is to propose basic guidelines for the Solid Waste Management (RS) at the Federal University of Pará, Campus of City University Professor. Jose da Silveira Netto / Bethlehem PA. The methodological procedures were based on literature review on the topic and some experiences in other universities. For the construction of the guidelines, such as the proposition of the institutionalization of integrated waste management, adoption of proposals with short and medium term surveys were carried out on the organizational structure and operational management of waste in the UFPA. It was found that the absence of a specific sector with competence and autonomy necessary for the management of waste in the UFPA, as well as lack of support from senior management to address these issues are factors that contribute to malpractice in relation to the environment throughout academic community. The results obtained in this research may provide support to the implementation of an Environmental Management System, with the creation of procedures to be adopted by the university community, which should be based on Environmental Policy to be implemented by the institution, resulting in benefits to those involved and society.